Prevalence and risk factors of emergence agitation among pediatric patients undergo ophthalmic and ENT Surgery: a cross-sectional study - Hong Yu; Xiaohui Sun; Ping Li; Xiaoqian Deng (BMC, 2023)
Abstract Background Some studies reported that pediatric patients undergoing otorhinolaryngology (ENT) and ophthalmic surgeries have higher incidences of emergence agitation (EA). Children with EA tend to carry the risk of self-harm, have longer periods of recovery and delayed hospital discharge. Consequently, EA needs to be monitored and risk factors ought to be emphasized to implement preventative measures. The objective of this study was to describe EA and to identify risk factors after pediatric ophthalmic or ENT surgery. Methods Between September 2021 and December 2021, a cross-sectional study was conducted in 100 children aged of 0-12 years who underwent ophthalmic or ENT surgery. The Watcha scale was used to observe and record EA, which was defined at levels of 3 or 4 at any time in the post-anesthesia care unit (PACU). The pain intensity was graded with the Face, Legs, Activity, Cry, Consolability (FLACC) Scale after surgery. Patient and surgery-related characteristics, the behavioral criteria of EA, the pharmacologic and non-pharmacologic interventions and recovery outcomes were objectively recorded. A binary logistic regression model was constructed to identify the associated factors of EA. Results From the 100 analyzed children, 58 were males and 42 were females, and 44 patients received ophthalmic surgery and 56 ENT surgery. The median age was 6 (IQR 4-7) years. The overall incidence of EA among pediatrics was 30% (34.5% for ENT and 24.4% for ophthalmic surgery). High preoperative modified Yale Preoperative Anxiety scale (m-YPAS) grade (OR = 1.19, 95%CI 1.06-1.33, P = 0.003) and high postoperative FLACC score (OR = 3.36, 95%CI 1.88-6.02, P < 0.001) were risk factors for EA. Conclusions This study identified that preoperative anxiety and postoperative pain are associated with EA in children after ophthalmic or ENT surgery. Preoperative anxiety assessment and management, and administration of adjunct analgesic treatments should be considered in the routine care.